Study of (Ag and TiO2)/water nanoparticles shape effect on heat transfer and hybrid nanofluid flow toward stretching shrinking horizontal cylinder - Rashid, Umair; Liang, Haiyi; Ahmad, Hijaz; Abbas, Muhammad; Iqbal, Azhar; Hamed, Y.S. (Results in physics, 2021)
•Behavior of nanoparticles shape on (Ag-TiO2)/water hybrid nanofluid flow.•Effect of suction and injection parameters.•Use of sphere, blade, and lamina shapes of Ag and TiO2.•The use of homotopy analysis method (HAM). This study reflects the behaviorof nanoparticles shape on (Ag-TiO2)/water hybrid nanofluid flow toward the horizontal permeable stretching shrinking cylinder. The effect of suction and injection parameters is also considered. Three different shapes (sphere, blade, and lamina) of Ag and TiO2 are used in this study. The boundarylayer equations of the problem are transformed to a setof non-linearODEs and the analytical solution of these non-linear ODEsis conducted. Thehomotopyanalysis method (HAM) is applied to findthe analytical resultsof the problem. The obtained results are also compared with the already published article by Sandeep et al.Spectacular characteristics of hybrid nanofluid flow quantities are carried out with a special focus on velocityf'η profile, temperature θηprofileand Nusselt numberNu. With the impact of pertinent parameters, the temperature and Nusselt number profiles show that the sphereshape nanoparticles have better temperature disturbance and heat transfer on hybrid nanofluid flow.